Capability Level Measurement of Information Systems Using COBIT 5 Framework in Garment Company - Deva Putra; Melissa Indah Fianty (Journal of Information System and Informatics, 2023)
The industrial company specializing in garment products uses information technology called ERP System to support daily activities. The information technology used is close to unavoidable problems. The problems in this company are internet and VPN connections being interrupted/disconnected, computer hardware damage, and user understanding of applicable information technology SOPs. To solve these problems, COBIT 5 was chosen to overcome existing problems by evaluating existing IT governance to produce and measure the level of capability and solution to problems. This research uses three processes, namely APO01, APO12, DSS03, which are obtained from the results of mapping the vision, mission, and problems faced by the company. Data were collected by interviewing resource persons: IT Managers, Accounting and Tax Managers, and the staff concerned. Moreover, they conducted a literature study on COBIT 5 to obtain the value of gap results and capability levels as recommendation guidelines. The result obtained is that the capability level is at level 1. The level gap is 1 level, comparing current conditions with the company's expected conditions. Ten recommendations are given to the company from the results of discussions to improve and develop information technology governance.